Berio - Osmond-Smith, David (New York Oxford university press, 1992)
Berio is one of the most widely performed and prodigiously productive of postwar composers. This book is nevertheless the first survey in any language of his work as a whole. Commentators on Berio's work have tended to concentrate on those aspects of his music that have strong extra-musicalassociations such as his use of words, sense of theatre, and interest in linguistics. While incorporating all of these, this account seeks to rectify the balance by focusing on the purely musical basis of Berio's work. Its chapters cover such areas as the basis of his musical language, hisinvolvement with Darmstadt, his work with computers at IRCAM and Tempo Reale, the importance of folk music, and his theatre works.